Measuring the Environmental Dimensions of Human Migration The Demographer's Toolkit - Fussell, Elizabeth (Global environmental change : human and policy dimensions, 2014)
In recent years, the empirical literature linking environmental factors and human migration has grown rapidly and gained increasing visibility among scholars and the policy community. Still, this body of research uses a wide range of methodological approaches for assessing environment-migration relationships. Without comparable data and measures across a range of contexts, it is impossible to make generalizations that would facilitate the development of future migration scenarios. Demographic researchers have a large methodological toolkit for measuring migration as well as modeling its drivers. This toolkit includes population censuses, household surveys, survival analysis and multi-level modeling. This paper's purpose is to introduce climate change researchers to demographic data and methods and to review exemplary studies of the environmental dimensions of human migration. Our intention is to foster interdisciplinary understanding and scholarship, and to promote high quality research on environment and migration that will lead toward broader knowledge of this association